Human Rights Guarantee for Prisoners in the Perspective of Correctional System in Indonesia - DM, Iklima Salsabil (Lex Scientia Law Review, 2017)
Correctional institutions are a part of the criminal justice system in Indonesia. The rise of criminal acts, both in the form of small and large scale crimes, has made the need for prisons in Indonesia continue to grow. The problem of overloading up to the non-fulfillment of the rights of the inmates of correctional institutions is a separate problem. Not to mention, various crime cases involving prisons, be it narcotics or other things. This paper analyzes how to guarantee human rights for convicts in the perspective of the correctional system in Indonesia.